'The Common Cormorant or Shag Lays Eggs Inside a Paper Bag'. A Cultural Ecology of Fish-eating Birds in Western Australia. (1st February 2003) - Sassoon, Joanna
This paper builds a history of the rise of ecological awareness of the Swan River in Perth, Western Australia through the cultural perceptions of fish-eating birds. A history of understandings of the specific habitat ecology is traced through the rise of scientific knowledge about fish-eating birds as competitors with fishermen. The impact of this changing awareness on the river ecology is discussed as well as how this scientific knowledge became subservient in the political domain to developmentalist ideology.